Ablation of Myeloid ADK (Adenosine Kinase) Epigenetically Suppresses Atherosclerosis in ApoE−/− (Apolipoprotein E Deficient) Mice. Issue 12 (December 2018) - Zhang, Min; Zeng, Xianqiu; Yang, Qiuhua; Xu, Jiean; Liu, Zhiping; Zhou, Yaqi; Cao, Yapeng; Zhang, Xiaoyu; An, Xiaofei; Xu, Yiming; Huang, Lei; Han, Zhen; et al.
Abstract : Objective—: Monocyte-derived foam cells are one of the key players in the formation of atherosclerotic plaques. Adenosine receptors and extracellular adenosine have been demonstrated to modulate foam cell formation. ADK (adenosine kinase) is a major enzyme regulating intracellular adenosine levels, but its functional role in myeloid cells remains poorly understood. To enhance intracellular adenosine levels in myeloid cells, ADK was selectively deleted in novel transgenic mice using Cre-LoxP technology, and foam cell formation and the development of atherosclerotic lesions were determined. Approach and Results—: ADK was upregulated in macrophages on ox-LDL (oxidized low-density lipoprotein) treatment in vitro and was highly expressed in foam cells in atherosclerotic plaques. Atherosclerotic mice deficient in ADK in myeloid cells were generated by breeding floxed ADK (ADK F/F ) mice with LysM-Cre (myeloid-specific Cre recombinase expressing) mice and ApoE −/− (apolipoprotein E deficient) mice. Mice absent ADK in myeloid cells exhibited much smaller atherosclerotic plaques compared with controls. In vitro assays showed that ADK deletion or inhibition resulted in increased intracellular adenosine and reduced DNA methylation of the ABCG1 (ATP-binding cassette transporter G1) gene. Loss of methylation was associated with ABCG1 upregulation, enhanced cholesterol efflux, and eventually decreased foam cell formation. Conclusions—: Augmentation of intracellular adenosine levels through ADK knockout in myeloid cells protects ApoE −/− mice against atherosclerosis by reducing foam cell formation via the epigenetic regulation of cholesterol trafficking. ADK inhibition is a promising approach for the treatment of atherosclerotic diseases. Abstract : Supplemental Digital Content is available in the text.